The sustained reduction-by-half of home advantage in the NHL, 1991-1992 to 2000-2001 - Jones, M. B. (SAGE open, 2019)
In the last decade of the 20th century, home advantage in the National Hockey League (NHL) fell by half, from 60% wins (or higher prior to 1991) to 55% wins, and has remained there until the present. This drop is much the largest and most abrupt of any change in home advantage in elite sports since the end of the Second World War. In addition, it is further complicated by two rule changes at the start of the decade. First, in 1991-1992 the NHL instituted instant video replay. Then the next year, 1992-1993, it imposed the instigator rule, which provided a game misconduct penalty (ejection from the game) for starting a fight and was followed by a prolonged drop in the frequency of fighting. Of the many theories of the home advantage, two are singled out as relevant to the fall in home advantage and possibly helpful in explaining it.